Temporal Trend Analysis of Historical Climatic Data at Northeastern Hilly Region of Bangladesh Using Mann-Kendall Test (Journal of Engineering Science, 2020)
An attempt has been implemented to find out the temporal trend of climatic data of average temperature and total rainfall for the study period 1980-2016 at North-Eastern Hilly Region in Bangladesh. The non-parametric Mann-Kendall test is used to analyze the trend of climatic data. The objective of the study is to investigate the trend variation in the North-Eastern hilly region. Results show that in monsoon season, both Sylhet and Srimangal meteorological stations experience a positive tendency with a rate of 0.037 and 0.0170C/year, respectively which are statistically significant at 99.9% level of significance. Monthly significant positive changes are found in all months except November, December and January for Sylhet while Srimangal indicates significant positive changes except July, September, October and November. The total rainfall at both the stations reveals decreasing trend during maximum seasons and months but the trend is not significant.Journal of Engineering Science 11(2), 2020, 19-25